Indoor TVOCs and CO2 levels in selected clinics of the Athens Dentistry School, Greece - Helmis, C.G.a; Flocas, H.A.a; Tzoutzas, J.b; Assimakopoulos, V.D.c; Panis, V.b; Sgouros, G.a; Apostolatou, M.a (WIT Transactions on Ecology and the Environment, 2006)
In this study an attempt is made to assess the indoor air quality status of clinics of the Athens University School of Dentistry with respect to VOCs and CC2. Measurements were collected for a period of approximately three months in three clinics with the aid of portable instrumentation. It was found that the levels of VOCs concentrations are high, being attributed to the use of acrylic substances and dental materials but also to the detergent products for cleaning the working surfaces. The VOCs levels depend on the number of occupants and the material use as well as on the number of open windows. The corresponding background values remain high in all clinics. The levels of the concentrations of CO2 are considered in general satisfactory as compared to the international standards, however, they can exceed the intervention limit at certain hours of the day, suggesting poor air renewal. The opening of the windows was found to improve the air quality status.
Keywords: Air quality; Athens [Attica]; Attica; carbon dioxide; conference proceeding; Eurasia; Europe; Greece; indoor air; instrumentation; measurement method; Southern Europe; volatile organic compound